Innovative Approaches in Computer Science and Information Technology Education (Texas Journal of Multidisciplinary Studies, 2023)
In the article, innovative modern information communication in the educational processthat the use of technologies has become one of the urgent tasks of today, the innovative approach of the pedagogue in the educational system and its effect on the effectiveness of the lesson, the general and specific aspects of innovative development, the ways of using modern innovative methods in the educational process held.